Childhood maltreatment and treatment outcome in psychotic disorders: a systematic review and meta‐analysis. (4th September 2019) - Thomas, S.; Höfler, M.; Schäfer, I.; Trautmann, S.
Abstract : Objective: Childhood maltreatment (CM) plays an important role in the aetiology and course of psychotic disorders and is associated with characteristics that could be relevant for treatment. We aimed to conduct a systematic review and meta‐analysis on the association between CM and treatment outcome in psychotic disorders. Methods: Treatment outcome was defined as change in psychotic symptoms or in social or occupational functioning between first and last reported measurement in the course of a pharmacological and/or psychological treatment. Results: Twelve treatment results from seven studies (636 patients, average treatment duration: 59.2 weeks) were included. CM was related to poorer treatment outcomes in psychotic disorders (OR = 1.51, 95% CI = [1.08, 2.10]). There is evidence that this association might increase with illness duration and increasing age and might be stronger in schizophrenia samples. Conclusions: Childhood maltreatment is highly understudied with regard to treatment outcome in psychotic disorders. The need for more studies is emphasized by the fact that this meta‐analysis reveals evidence for a poorer treatment response in patients with CM. If this association is confirmed, the identification of patients with CM and the consideration of associated clinical and biological conditions could contribute to improve treatment outcome in psychotic disorders.